Describing Manipulative Media Use in Mathematics Learning: Students' Understanding, Engagement, and Teacher Guidance - Kurniawati, Anna; Riyadi, Riyadi; Triyani, Septi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
This study aims to describe students’ experiences and perceptions of using manipulative media in learning whole-number addition and subtraction in elementary school. A descriptive qualitative approach was employed, involving 15 second-grade students and one classroom teacher selected through purposive sampling. Data were collected through interviews, open-ended questionnaires, and participant observation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings show that the use of manipulative media enhances students’ conceptual understanding by transforming abstract mathematical concepts into concrete representations, while also increasing engagement, motivation, and self-confidence in learning mathematics. Most students expressed positive perceptions, indicating that manipulative media helped them visualize and understand mathematical operations more easily; however, some students experienced initial difficulties, highlighting the importance of teacher guidance. The study implies that manipulative media can be an effective instructional strategy to improve mathematics learning in elementary schools, although its effectiveness depends on proper implementation and teacher support. This study is limited by a small sample size and short duration; therefore, future research is recommended to involve larger and more diverse participants and longer observation periods to obtain more comprehensive findings.